(untitled) (Historia, 2021)
The wheel was late to arrive in the South African Lowveld, as it was only in the 1830s that the first explorers and emigrants ventured far inland in their ubiquitous ox wagon. Describing the events as they unfolded and the people involved, this book gives an accurate and concise history of the forgotten tracks and trails of the Escarpment and the Lowveld in South Africa, during the period leading up to the establishment of the Eastern Railway line to Delagoa Bay (1891). The author, Gerrit Haarhoff is a member of the Mpumalanga Heritage Society and his book is a work of gigantic proportions with 720 high quality colour photographs, with more than 60 maps, the stories of a people driven by trade, who dared to create a living against fearful and invisible odds, unfold. With old maps and charts and using the latest drone technology, forgotten roads were identified during his field trips as they crossed mountain passes and forded drifts.